A practical guide to SysML : the systems modeling language - Friedenthal, Sanford; Moore, Alan, 1961-; Steiner, Rick (Consulting engineer) (MK/OMG Press., 2015)
A Practical Guide to SysML, Third Edition, fully updated for SysML version 1.4, provides a comprehensive and practical guide for modeling systems with SysML. With their unique perspective as leading contributors to the language, Friedenthal, Moore, and Steiner provide a full description of the language along with a quick reference guide and practical examples to help you use SysML. The book begins with guidance on the most commonly used features to help you get started quickly.